2010
DOI: 10.1093/nar/gkq1177
|View full text |Cite
|
Sign up to set email alerts
|

Structures of carbon catabolite protein A–(HPr-Ser46-P) bound to diverse catabolite response element sites reveal the basis for high-affinity binding to degenerate DNA operators

Abstract: In Gram-positive bacteria, carbon catabolite protein A (CcpA) is the master regulator of carbon catabolite control, which ensures optimal energy usage under diverse conditions. Unlike other LacI-GalR proteins, CcpA is activated for DNA binding by first forming a complex with the phosphoprotein HPr-Ser46-P. Bacillus subtilis CcpA functions as both a transcription repressor and activator and binds to more than 50 operators called catabolite response elements (cres). These sites are highly degenerate with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 56 publications
2
78
1
Order By: Relevance
“…The two proteins have similar DNA affinities, with K d (dissociation constant) values of approximately 5 to 10 nM for the cre sequence in the ackA gene (4,36). Both types of CcpA protein at similar concentrations were also reported to achieve protection from DNase I digestion in the ilvB promoter (52,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two proteins have similar DNA affinities, with K d (dissociation constant) values of approximately 5 to 10 nM for the cre sequence in the ackA gene (4,36). Both types of CcpA protein at similar concentrations were also reported to achieve protection from DNase I digestion in the ilvB promoter (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of HprK is triggered by accumulation of fructose-1,6-biphosphate, whose cellular concentrations are increased by the incorporation of a preferred sugar such as glucose. CcpA binds to a degenerate pseudopalindromic sequence known as the cre (catabolite-responsive element) sequence (4). CcpA functions negatively and positively for gene transcription, and its function is determined by the location of the cre sequence in many cases (2).…”
mentioning
confidence: 99%
“…The cre consensus sequence was determined in B. subtilis and consists of a pseudopalindromic sequence (WTG 3 NNARC 8 G 9 N WWWC 14 AW, where W stands for A or T, R for A or G, and N for any base). It has recently been reported that the central C 8 G 9 and G 3 C 14 residues are the only completely conserved nucleotides within experimentally confirmed cre sites (39,40). Interestingly, it has been shown that the location of a cre site upstream from the promoter, within the promoter, or downstream from it determines whether CcpA acts as a transcriptional activator (CCA) or a repressor (CCR), respectively (18).…”
mentioning
confidence: 99%
“…The consensus sequence of cre has been determined to be TGWAANCGNTNWCA in Bacillus subtilis , a model organism of Gram-positive bacteria, in which N represents any base and W represents A or T (8). Additional cre s identified later in B. subtilis also closely match this consensus sequence (7, 9). However, it has recently been found that, in some cases, CcpA employed two different binding motifs (one is a typical cre and the other one is an atypical cre ) to regulate the central carbon metabolism (10).…”
Section: Introductionmentioning
confidence: 52%
“…It is known that CcpA executes its regulation via binding to a so-called catabolite-responsive element ( cre ) within the promoter or protein-coding regions of the target genes (7). The consensus sequence of cre has been determined to be TGWAANCGNTNWCA in Bacillus subtilis , a model organism of Gram-positive bacteria, in which N represents any base and W represents A or T (8).…”
Section: Introductionmentioning
confidence: 99%